Analysis of the distinction between two key leadership attributes : charisma and vision. - Selvaraju, S. (2008)
Since leadership is one of the most studied and least understood topics of any in the social sciences, any study on this topic is bound to be challenging and interesting. Books on leadership are often as majestically useless as they are pretentious. Leadership is like the Abominable Snowman, whose footprints are everywhere but who is nowhere to be seen. Hence this topic intrigued us. We knew from the start that though we are not on an uncharted territory, our study on this topic will definitely let us experience and explain novelty in some form or another. It was this thought that led us to work on this topic.